Scalable fabrication of COF membranes for aliphatic/aromatic separation of crude oil - Li Cao; Shuhao An; Bingbing Yuan; Zhen Li; Vasilios G. Samaras; Ting Xu; Xixiang Zhang; Huabin Zhang; Zhiping Lai (Science, 2026)
Distillation has been the cornerstone of crude oil refining for more than a century, relying on boiling point differences for fractionation. Although effective, it is highly energy-intensive and lacks the precision to separate specific hydrocarbon classes. We report crystalline covalent organic framework (COF) membranes with well-defined micropores and alkyl-functionalized frameworks that combine molecular sieving with preferential affinity to enrich aliphatics. An electric field–assisted roll-to-roll process enabled scalable fabrication of continuous membranes. These COF membranes enriched aliphatics to >95% and delivered permeance orders of magnitude higher than amorphous polymers in Arabian Light crude oil. A crude oil permeance of 0.34 liters m −2 hours −1 bar −1 with >90% aliphatics enrichment was achieved using industrial-standard 1812 membrane modules, demonstrating a lower energy demand than distillation.